(untitled) (The Chittagong University Journal of Science, 2022)
The main focus of this research study is to investigate the determining factors affecting the awareness of HIV/AIDS among ever married women in Bangladesh. To accomplish this task fruitfully, the study uses the nationally representative BDHS 2014 data set. The finding of this study illustrates that about 70% of the respondents have heard of AIDS. Among the respondents who have heard of AIDS, 97.4% and 92.5% of them have HIV/AIDS transmission and prevention knowledge respectively. Bivariate analysis states that the variables type of place of residence, division, respondents’ education and access to mass media are significantly associated with the awareness of HIV/AIDS and also its transmission and prevention knowledge. The multivariate hierarchical logistic regression analysis reveals that respondents’ education has a significant impact on HIV/AIDS awareness and its transmission and prevention knowledge. The odds ratio in all the models indicates that respondents who are highly educated and have access to mass media are more knowledgeable about HIV/AIDS. Type of place of residence and region has significant effect on the awareness of HIV/AIDS, and also its transmission and prevention knowledge. Age of the respondents, husband education and occupation also have significant impact on the awareness of HIV/AIDS. Finding of this study further reflects that use of contraceptives is a predominant significant factor influencing the awareness of HIV/AIDS. Therefore, based on the findings it can be concluded that appropriate steps should be launched across the country to raise the awareness level of such a deadly disease for the reduction of its spread in Bangladesh. The Chittagong Univ. J. Sci. 43(1): 93-112, 2021